Network Power: Japan And Asia - Peter J. Katzenstein, Takashi Shiraishi (Cornell University Press, 1996)
This book examines regional dynamics in contemporary east and southeast Asia, scrutinizing the effects of Japanese dominance on the politics, economics, and cultures of the area.